Wokół problemów semantycznej kategorii określoności/nieokreśloności i struktury tematyczno-rematycznej w języku bułgarskim i polskim - Banasiak, Jakub (Slavica Lodziensia, 2019)
The paper discusses the interplay between the semantic category of definiteness/indefiniteness and thematic-rhematic structure. Special attention is paid to the semantic requirements that must be met by phrases that may undergo thematization. The “thematizability” of both general and unique phrases is stressed and considered an argument in favour of the common treatment of generality and uniqueness.